History of stroke in patients with heart failure: prevalence, baseline characteristics and clinical outcomes. (3rd October 2022) - Yang, M; Kondo, T; Butt, J H; Abraham, W T; Desai, A S; Kober, L; Martinez, F A; Packer, M; Pfeffer, M A; Rouleau, J L; Solomon, S D; Zile, M R; et al.
Abstract: Background: Stroke is an important but neglected comorbidity in patients with heart failure (HF). Little is known about the characteristics and outcomes of HF patients with a history of stroke. Purpose: To examine the prevalence of prior stroke in patients with HF and reduced ejection fraction (HFrEF) and HF with preserved ejection fraction (HFpEF), the clinical characteristics of patients with a history of stroke, and the clinical outcomes in patients with prior stroke compared to those without. Methods: Individual patient data analysis using three recent HFrEF trials (ATMOSPHERE, PARADIGM-HF, and DAPA-HF) and HFpEF trials (CHARM-Preserved, I-Preserve, TOPCAT-Americas, and PARAGON-HF). Cox regression was used to analyze clinical outcomes. Results: Among 20159 HFrEF patients enrolled, 1683 (8.3%) had a history of stroke and among the 13252 patients with HFpEF 1287 (9.7%) had a prior stroke. Compared to patients without stroke, those with stroke were slightly older and more likely to have a history of hypertension, myocardial infarction, atrial fibrillation, diabetes, carotid artery disease, and peripheral artery disease (for both HFrEF and HFpEF). Patients with a history of stroke had worse NYHA class and KCCQ scores, and a higher rate of fatigue; they also had a higher median NT-proBNP level and lower eGFR than those without prior stroke (whether HFrEF or HFpEF). Systolic BP, pulse pressure and LVEF did not differ susbtantialy between patients with and without a history of stroke. The table shows outcomes according to history of stroke or not, stratified by LVEF phenotype. During follow-up, all fatal and non-fatal outcomes were significantly more common in patients with a history of stroke. The augmentation of risk tended to be greater in patients with HFpEF than HFrEF, but was not statistically different. Conclusion: Approximately 1 in 11 patients in recent HF trials had a history of stroke and these patients were at higher risk of fatal and non-fatal events than those without prior stroke. HF hospitalization as well as atherothrombotic events (myocardial infarction and stroke) were more common among patients with prior stroke – patients with prior stroke had at least 30% higher risk of all events examined, regardless of LVEF, and more than double incidence of repeat stroke. Funding Acknowledgement: Type of funding sources: Other.